Multi‐slack power flow for islanded microgrids with radial and meshed topologies - Elson Natanael Moreira Silva; Anselmo Barbosa Rodrigues; Maria daGuia da Silva (IET Generation, Transmission & Distribution, 2020)
This study proposes a new power flow formulation for islanded microgrids. The proposed power flow is based on the effect of the superposition principle and the solution of a small non‐linear subproblem to determine the frequency of the microgrid and the voltage magnitude in the angular reference node in each iteration. These variables are determined by considering the following equations in the non‐linear subproblem: active and reactive power balance equations and specified phase at the angular reference node. The application of the superposition principle allowed to obtain two versions of the proposed technique: one for radial networks − based on the current summation method − and another for meshed networks − based on the Gauss‐Zbus method. Therefore, the iterative framework prosed in this study expands in a simple and integrated way the two most commonly used power flow methods in conventional distribution networks for islanded microgrids. The tests in microgrids with 33, 310 and 1438 nodes showed that the proposed approach has the same accuracy as Newton–Raphson algorithm, but with significantly lower computational cost in large scale microgrids. In addition, the proposed method for island microgrid showed good accuracy and convergence for the most common load models applied in power flow studies of islanded microgrids.